2011
DOI: 10.1002/chir.20879
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective metabolism of benalaxyl in liver microsomes from rat and rabbit

Abstract: Benalaxyl (BX), methyl-N-phenylacetyl-N-2,6-xylyl alaninate, is a potent acylanilide fungicide and consist of a pair of enantiomers. The stereoselective metabolism of BX was investigated in rat and rabbit microsomes in vitro. The degradation kinetics and the enantiomer fraction (EF) were determined using normal high-performance liquid chromatography with diode array detection and a cellulose-tris-(3,5-dimethylphenylcarbamate)-based chiral stationary phase (CDMPC-CSP). The t(1/2) of (-)-R-BX and (+)-S-BX in rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…The metabolism of benalaxyl in rats and rabbits liver microsomes was similar to ethofumesate. In rat liver, microsomes (+)‐ S ‐ benalaxyl was degraded faster than its antipode; on the contrary, (−)‐ R ‐ benalaxyl was degraded faster than (+)‐ S ‐ benalaxyl in rabbit liver microsomes . The P450 family of enzymes can be inhibited, activated, or induced by concomitant xenobiotic treatment, so the xenobiotic–xenobiotic interactions may alter the enantioselective behavior of enantiomers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The metabolism of benalaxyl in rats and rabbits liver microsomes was similar to ethofumesate. In rat liver, microsomes (+)‐ S ‐ benalaxyl was degraded faster than its antipode; on the contrary, (−)‐ R ‐ benalaxyl was degraded faster than (+)‐ S ‐ benalaxyl in rabbit liver microsomes . The P450 family of enzymes can be inhibited, activated, or induced by concomitant xenobiotic treatment, so the xenobiotic–xenobiotic interactions may alter the enantioselective behavior of enantiomers.…”
Section: Resultsmentioning
confidence: 99%
“…In rat liver, microsomes (+)-S-benalaxyl was degraded faster than its antipode; on the contrary, (À)-R-benalaxyl was degraded faster than (+)-S-benalaxyl in rabbit liver microsomes. 25 The P450 family of enzymes can be inhibited, activated, or induced by concomitant xenobiotic treatment, so the xenobiotic-xenobiotic interactions may alter the enantioselective behavior of enantiomers. These important areas are not considered in detail in this concept paper.…”
Section: Gender-related Differences In Metabolism Of Hexaconazolementioning
confidence: 99%
“…The procedure of preparation of rabbit hepatic microsomes from rabbits (Japanese white rabbit, male, Approximately 2 kg, provided by the Experimental Animal Research Institute of China Agriculture University) followed the method of Zhang et al12 and the microsomes were immediately stored at −80°C. Hepatic microsomal activity was determined according to the method of Bradford with BSA as the standard.…”
Section: Methodsmentioning
confidence: 99%
“…In the study of environmental behavior, the researchers reported differences in dissipation rate of the two enantiomers in plants such as tomato, tobacco, sugar beet, capsicum, cucumber, and Scenedesmus obliquus . Meanwhile, the stereoselective degradation of benalaxyl was also found in animals such as earthworm, rat, and rabbit . More important, the enantioselective toxicity of benalaxyl was investigated by researchers.…”
mentioning
confidence: 99%
“…17,22 Meanwhile, the stereoselective degradation of benalaxyl was also found in animals such as earthworm, rat, and rabbit. 20,23,24 More important, the enantioselective toxicity of benalaxyl was investigated by researchers. It was found that the two enantiomers of benalaxyl exhibited different acute toxicity to earthworm (Eisenia fedtia) and freshwater algae (Scenedesmus obliquus), and R-(À)benalaxyl showed much higher toxicity to both organisms.…”
mentioning
confidence: 99%